THE IMPORTANCE OF CARDIORESPIRATORY FITNESS AND PHYSICAL ACTIVITY AMONG ADULTHOOD STAGES-REVIEW - Dan Alexandru SZABO (Cluj University Press, 2021)
Introduction: Adulthood is a period of development and transformation, though it may not be as dramatic as childhood and adolescence. Physical changes, for example, from youth to adolescence, are transformative. The body proliferates and develops secondary sexual characteristics as adolescence progresses. Exercise training for the elderly has been linked to a variety of health benefits, including a reduction in cardiovascular mortality. Changes in the balance of the cardiac autonomic nerves result in an increase or relative innervation of the vagus nerve, an explanatory mechanism that may be involved after exercise. Regular physical activity has also been linked to improving mental health (for example, reducing stress, anxiety, and depression). Mental health is critical for preventing and managing cardiovascular disease, but it also impacts other chronic diseases (such as diabetes, osteoporosis, hypertension, obesity, cancer, and depression). Conclusions: Finally, this review unifies the relationship between physical activity, cardiorespiratory health, and adulthood across the life span. In adulthood, changes in daily physical activity have a significant impact on overall health and well-being. As people's corporeal and psychological health care deteriorates with age, regular physical activity becomes crucial for well-being. REZUMAT. Importanța fitness-ului cardiorespirator și a activității fizice în rândul adulților-review. Introducere: Vârsta adultă este o perioadă de maturizare și schimbare, deși poate să nu fie la fel de dramatică precum copilăria și adolescența. Schimbările fizice, de exemplu, de la copilărie la adolescență, sunt transformatoare. Antrenamentul pentru vârstnici a fost legat de o varietate de beneficii pentru sănătate, inclusiv o reducere a mortalității din cauza bolilor cardiovasculare. Modificările în echilibrul nervilor autonomi cardiaci au ca rezultat o creștere sau o inervație relativă a nervului vag, un mecanism explicativ care poate fi implicat după efort. Activitatea fizică regulată a fost, de asemenea, legată de îmbunătățirea sănătății mintale (de exemplu, reducerea stresului, anxietății și depresiei). Sănătatea mintală este esențială pentru prevenirea și gestionarea bolilor cardiovasculare, dar are un impact și asupra altor boli cronice (cum ar fi diabetul, osteoporoza, hipertensiunea, obezitatea, cancerul și depresia). Concluzii: În cele din urmă, această recenzie unifică relația dintre activitatea fizică, sănătatea cardiorespiratorie și vârsta adultă de-a lungul ontogenezei. La vârsta adultă, schimbările în activitatea fizică zilnică au un impact semnificativ asupra sănătății și bunăstării generale. Pe măsură ce sănătatea fizică și mentală a oamenilor se deteriorează odată cu vârsta, activitatea fizică regulată devine crucială pentru obținerea bunăstării. Cuvinte cheie: Activitate fizică, Fitness cardiorespirator, vârsta adultă.